The Relationship Between Protein Whey Milk Consumption and The Occurrence of Acne Vulgaris in Adolescents Aged 18-21 Years - Timotius, Timotius; Charity Kamalo, Angelica Joana; Eunike, Debora; Titanic, Pussof Yayazucah; Priyanto, Teguh; Ã‡elik, Semih (Poltekkes Kemenkes Tanjung Karang, 2023)
Acne vulgaris is an inflammation that occurs in the pilosebaceous gland with a prevalence of 18-21 years affected adolescents. This study aimed to determine the relationship between consumption of whey protein and the incidence of acne vulgaris. The research design was a literature review by searching medical scientific articles. Over 7,408 articles were found when searching for